Pengaruh Internet Dan Motivasi Belajar Terhadap Hasil Belajar Kelas X SMK PGRI 2 Kediri - Aini Fortunila Fitrianti; Afandi, Tjetjep Yusuf; Prastyaningtyas, Efa Wahyu (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to determine the effect of internet and learning motivation on the learning outcomes of class X students majoring in Accounting. This research approach uses quantitative, the research technique uses causality. The population and sample are students of class X majoring in Accounting, totaling 30 students. Sampling technique used in this study is purposive sampling. Methods of data collection using observation and questionnaires. Data analysis used classical hypothesis testing, multiple regression analysis testing, certainty testing and hypothesis testing. Research results show that: 1) internet use affects learning outcomes 0.002<0.05, 2) learning motivation affects learning outcomes 0.039<0.05, 3) internet use and learning motivation has an effect on learning outcomes simultaneously 0.00 <0.05. Coefficient of determination = 0.466 = 47%,. Therefore, it can be conclusion that there is an effect of internet and learning motivation about learning outcomes of class X majoring in accounting.